Relative Effectiveness of Alternative Microfinance-driven Poverty Alleviation Programs in Bangladesh. - Chowdhury, Tamgid Ahmed (Cambridge Scholars Publishing, 2013)
In general, the effectiveness of microfinance-driven poverty-alleviation programs run by Government Organizations (GOs) and Non-Government Organizations (NGOs) in developing countries, such as Bangladesh, is assessed by repayment rates, the number of beneficiaries, the area coverage, the amount of loans disbursed, the cost of operations, profitability, and the financial sustainability of the projects. This study argues that these methods are quite restrictive since none of them reflect the pe ...